The Impact of Acne, Atopic Dermatitis, Skin Toxicities and Scars on Quality of Life and the Importance of a Holistic Treatment Approach - Dreno B; Amici JM; Demessant-Flavigny AL; Wright C; Taieb C; Desai SR; Alexis A (Dove Medical Press, 2021)
Brigitte Dreno,1 Jean Michel Amici,2 Ann Laure Demessant-Flavigny,3 Charlotte Wright,4 Charles Taieb,5 Seemal R Desai,6 Andrew Alexis7 1Dermatology Department, CHU Nantes, CIC 1413, CRCINA, Nantes University, Nantes, Pays de la Loire, France; 2Dermatology Department, Bordeaux University Hospital, Bordeaux, Nouvelle-Aquitaine, France; 3La Roche-Posay Dermatological Laboratoires, Levallois-Perret, France; 4Speak the Speech Consulting, Asnières-sur-Seine, Ile-de-France, France; 5Patients Priority Department, European Market Maintenance Assessment, Fontenay Sousbois, Ile-de-France, France; 6Department of Dermatology, The University of Texas Southwestern Medical Center & Innovative Dermatology, Dallas, TX, USA; 7Skin of Color Center, Mount Sinai St. Luke’s and Mount Sinai West, Icahn School of Medicine at Mount Sinai, New York, NY, USACorrespondence: Charles TaiebPatients Priority Department, European Market Maintenance Assessment, Fontenay Sousbois, Ile-de-France, FranceTel +33 771772100Email Charles.taieb@emma.clinicAbstract: Skin conditions such as acne, atopic dermatitis, skin toxicity from oncology treatment, and scars are among the most common health conditions and negatively impact quality of life (QoL). Yet the physician perception of this impact often varies greatly from the patient perception. This is important because patient illness perception is closely linked with seeking help and treatment adherence behaviors. The objective of this review is to better understand the impact of these four highly prevalent skin conditions on QoL including their health-related economic factors to improve treatment outcomes. The literature search included literature published on QoL with acne, atopic dermatitis, scars (from any cause) and skin toxicities on PubMed between 2015 and 2020. We found that patients with skin conditions have a much higher frequency of altered QoL and psychological distress than those without. Also, skin conditions negatively impact self-image and can cause feelings of isolation, loneliness, lower self-esteem, and lower body satisfaction. Additionally, physical discomfort adds to the psychological distress. These physical and psychological impacts are an enormous financial burden on patients, their families and society. We found evidence that holistic treatment including treating the skin condition itself, providing wider peer and psychological support as well as shared decision-making, therapeutic patient education and dermatologist involvement improves outcomes. Holistic history-taking, checklists, or the use of more formal QoL scoring tools can be incorporated into routine consultations to better assess patient well-being and provide clinicians with important information for adapting treatment to individual patient requirements. In conclusion, this review highlights the overall impact of skin conditions (including psychological and QoL impacts) and the importance of providing holistic care to optimize treatment outcomes. A comprehensive QoL screening tool would be useful to help provide patient-centered treatment.Keywords: quality of life, acne, atopic dermatitis, scars, burns, skin toxicities